Cadmium and lead uptake by wild swamp eel in the populous river - N. Nurhasanah; L. Sulistyowati; E. Riani; M. Cordova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: For enhanced environmental management of the Ciliwung River, toxic pollutions such as cadmium dan lead data are required. Cadmium and lead have widespread industrial applications. However, cadmium and lead are poisonous and classified as cancer-causing non-essential elements. Moreover, cadmium and lead accumulation in Ciliwung River-caught eels has not yet been examined. Consequently, it is essential to acquire the gathered data from this study. The primary objective of this study was to explore the accumulation of cadmium and lead in sediments and eel organs along the Ciliwung River and to estimate the weekly cadmium and lead intake from eel consumed by the people.METHODS: Sediment and eel samples were collected at six sampling locations ranging from the upstream, midstream, and downstream regions. Method of 3051a of the United States Environmental Protection Agency was applied to analyze the metal yield from the sediment samples and targeted eel organs (gills, digestive tract, and flesh). In addition, quality control and quality assurance standards were employed, and Certified Reference Materials were used to ensure the quality of data and instruments.FINDINGS: The average concentrations of cadmium (0.7825±0.3768 milligram per kilogram) and lead (36.9333±14.9040 milligram per kilogram) were greater than their natural levels. The average cadmium concentration in riverine sediment was below the interim sediment quality guidelines. However, the lead concentration exceeded the guidelines. The cadmium and lead accumulation patterns in the sediment and eels were found to be lowest in the upstream and found increased in the downstream are. In this case, the gills acquired the most concentration of cadmium (1.4571±0.3433 microgram per gram) and lead (43.2489±18.6775 microgram per gram). The fact that eel gills accumulated the highest cadmium and lead indicates the presence of heavy metals in their environment. The accumulation of cadmium and lead in the eel surpassed the permitted levels. According to the Provisional Tolerable Weekly Intake estimation, this research showed 0.0328 milligram/week for the cadmium and 1.2826 milligram/week for the lead.CONCLUSION:  The prevalence of cadmium and lead in riverine sediments and eels in the Ciliwung River is believed to be predominantly the result of inefficient wastewater management. However, cadmium and lead pollution must be handled with extreme caution because it interferes with the physiological processes of the biota, hence decreasing the population of eels and posing a health risk if consumed. In general, Asian swamp eels from the Ciliwung River are still edible. As a result, it is hoped that enhanced management will reduce the number of pollutants entering the riverine ecosystem.